Volatility and conditional distribution in financial markets - Klaus Abberger (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
There are various parametric models to analyse the volatility in time series of financial market data. For maximum likelihood estimation these parametric methods require the assumption of a known conditional distribution. In this paper we examine the conditional distribution of daily DAX returns with the help of nonparametric methods. We use kernel estimators for conditional quantiles resulting from a kernel estimation of conditional distributions.
Keywords: 330; Börsenkurs; Kapitaleinkommen; Zeitreihenanalyse; Theorie; Deutschland